DYNAMIC BEHAVIOR OF THIN-WALLED ELEMENTS OF AIRCRAFT MADE OF COMPOSITE MATERIALS, EXCITED BY HEAT SHOCK - Starovoitov, Eduard I.; Leonenko, Denis V.; Orekhov, Alexander A. (Journal of Applied Engineering Science, 2020)
To improve the performance characteristics of modern aerospace systems, research is conducted and expensive programs are being carried out to provide for reducing the weight of the aircraft structure through the use of new, more promising materials, which include the so-called composite materials. Special attention is paid to the dynamic behaviour of composite structures under the influence of high-intensity heat fluxes of various physical nature. The paper considers the dynamic behaviour of composite structures of modern aerospace systems under the influence of high-intensity heat fluxes. As an example, the axisymmetric transverse vibrations of a composite circular plate connected to an elastic base, excited by thermal shock, are investigated. The plate material is modelled with a three-layer composite. To describe the kinematics of an asymmetric plate pack, the hypotheses of a broken normal are accepted. In thin bearing layers, Kirchhoff's hypotheses are valid. In a relatively thick lightweight core, the normal does not change its length, remains rectilinear, but rotates through some additional angle. The base reaction is described by the Winkler model. The statement of the initial-boundary value problem is given. The analytical solution is obtained as a series expansion in terms of eigenfunctions. Its numerical parametric analysis is carried out.
Keywords: composite round plate; vibration; heat flux; elastic base